Europe's carbon border adjustment mechanism: Time to go back to the drawing board - Fredrik Erixon (European Centre for International Political Economy (ECIPE), 2021)
This Policy Brief takes stock of the global and European trade and carbon-emission effects from CBAM. It argues that the current design of the CBAM is not good enough and, ultimately, that there are risks that it will dent the positive effects on global carbon emissions that come from a lower cap on carbon emissions in Europe. These effects will happen through trade and the reallocation of production - and from retaliatory responses from countries that will be negatively affected by the CBAM.
Keywords: 330; Treibhausgas-Emissionen; EU-Emissionshandel; Emissionshandel; Internationale Umweltpolitik